Mental Health Integration in Geriatric Patient-Aligned Care Teams in the Department of Veterans Affairs - Moye, Jennifer (Am J Geriatr Psychiatry, 2018)
OBJECTIVES: To inform geriatric mental health policy by describing the role of behavioral healthcare providers within a geriatric patient-aligned care team (GeriPACT), a patient-centered medical home model of care within the Veterans Health Administration (VHA), serving older veterans with chronic disease, functional dependency, cognitive decline, and psychosocial challenges, and/or those who have elder abuse, risk of long-term care placement, or impending disability. METHODS: The authors used mixed methods, consisting of a national survey and site visits between July 2016 and February 2017, at VHA outpatient clinics. The participants, 101 GeriPACTs at 44 sites, completed surveys, and 24 medical providers were interviewed. A standardized survey and semi-structured interview guide were developed based on the program handbook, with input from experts in the VHA Office of Geriatrics and Extended Care Services, guided by the Consolidated Framework for Implementation Science Research. RESULTS: Of surveyed GeriPACTs, 42.6% had a mental health provider on the team—a psychiatrist (28.7%) and/or psychologist (23.8%). Of these, the mean was 0.27 full-time equivalent psychiatrists and 0.44 full-time equivalent psychologists per team (suggested panel = 800 patients). In surveys, teams with behavioral health providers were more likely to manage psychosocial χ(2) = 8.87, cognitive χ(2) = 8.68, and depressive χ(2) = 1185 conditions in their panel than those without behavioral health providers. CONCLUSION: GeriPACT mental health integration is less than 50%. Population differences between general primary care and geriatric primary care may require different care approaches and provider competencies and need further study.